Odpowiedzi

2010-03-10T19:31:40+01:00
Najlepsza Odpowiedź!
2010-03-10T19:31:47+01:00
A) (3x + 5) + (7x - 2 + 6) + (- x + y - 1) = 3x + 5 + 7x - 2y + 6 - x + y - 1 = 9x + 10+y .
b) - (4a + 2b - 1) + (- 3a - 3b + 4) - (6a + 3) = - 4a - 2b + 1 + 7x - 2y + 6 - x - y +1 = -4a - 2b + 6x + 3y +1 .
c) - ∑ - (3x + 2y) | - ( -2x - 2y ) + ( -5x - 3y) = - 3x - 2y - 2x + 2y + ( -5x - 3y) = 0 + 3y .
d) 6xy - (2xy + 3y) + (xy + 4x - 7y) = 6xy - 2xy - 3y - xy + 4x - 7y = 3xy + 11y + 4x
2 3 2
2010-03-10T19:32:11+01:00
A) 3x+5+7x+4-x+y-1=
9x+8+y
b) -4a-2b+1-3a-3b+4-6a-3=
-13a-5b-2
d) 6xy-2xy-3y+xy+4x-7y=
5xy-10y+4x